Characterization of tribological materials - Glaeser, William A.; Brundle, C. Richard (New York Momentum Press, LLC, 2012)
Tribology is a discipline concerned with contacting surfaces. This book shows how surface analytical techniques can be used together with the knowledge of basic principles of tribology to help understand failure processes. For instance, Chapter 8 shows how precision ball bearings and their critical lubrication requirements require knowledge of lubricant behavior of very thin films and surface reaction (boundary lubrication) for reliable performance. Thus if a bearing material is altered, it may be necessary to determine its effect on surface chemistry of lubricants. Surface analysis, including wear scar analysis, can be factored into test programs as a supplemental component or as an integral part of the set up.
1. Introduction -- 2. The role of adhesion in wear -- 3. Friction -- 4. Adhesive wear -- 5. Abrasive wear -- 6. Boundary lubrication -- 7. Magnetic recording surfaces -- 8. Surface analysis of precision ball bearings -- 9. Atomic force microscope nanofriction. -- Appendices: technique summaries.
First published by Butterworth-Heinemann in 1993.
Includes bibliographical references and index.
Also available in eprint.
Keywords: Tribology; Materials -- Mechanical properties